Relationship between pest grasshopper densities and climate variables in the southern Pampas of Argentina. Issue 5 (31st October 2022) - Mariottini, Y.; Marinelli, C.; Cepeda, R.; De Wysiecki, M. L.; Lange, C. E.
Abstract: Grasshoppers are one of the most predominant insects in the grasslands of the southern Pampas. In this region, Dichroplus elongatus, Dichroplus maculipennis, Dichroplus pratensis and Borellia bruneri are the most abundant species and have the greatest economic importance. This study aimed to assess the relationship between temporal changes in the density of these species and climate variables associated with temperature and rainfall over an 11-year study period., We monitored 22 sites in different areas of Laprida county from 2005 to 2016. A total of 25 grasshopper species were collected. The most abundant species were D. maculipennis and B. bruneri which reached the highest densities from 2008–2009 to 2010–2011. The rainfall accumulated from September (RAS) to the sampling date and the number of rainy days (RD) largely explained the density variation of B. bruneri . Besides RD and RAS, winter rainfall, rainfall accumulated from October to the sampling date, and thermal amplitude of October (TAO) influenced the density of D. maculipennis . Our results indicated that seasons with less rainfall and fewer RD favored these two species' abundance. We identified that the RD and TAO contributed significantly to variations in the density of D. elongatus. In contrast to the other two species, we recorded D. elongatus in seasons with high rainfall and high RD. A better understanding of the climate influence on the life cycle of these economically important insects may identify key factors in their population dynamics which in turn may improve management options.